Religious Education, Secular Pluralism, and Multicultural Citizenship: A Comparative Study of Public High Schools in Indonesia and the United States - Supandi, Ahmad; Masyhuri, Muhammad; Sa’diyah, Muzayyanah; Fransisca, Amela Salwa (Journal of Islamic Education Research, 2026)
This study examines how religious education and secular pluralism shape the formation of multicultural citizenship in public high schools in Indonesia and the United States through a comparative lens. It aims to compare how two contrasting constitutional frameworks, religiously integrated public education and constitutionally secular public education, influence civic formation within plural school environments. The study employed a qualitative multiple-case comparative design involving four public high schools, two in Indonesia and two in the United States. Data were collected through semi-structured interviews with teachers, administrators, and students, as well as classroom observations conducted both onsite and online, and document analysis. The findings suggest that multicultural citizenship is not solely determined by the presence or absence of religious instruction, rather it is shaped by the interaction between constitutional frameworks and pedagogical practices within schooling context. In Indonesia, religious education operates within a constitutional framework that recognises religion as a foundation element of national identity, whereas in the United States, religious instruction is formally excluded from public schooling. In both contexts, dialogical pedagogy emerges as the key mediating mechanism that translates institutional structures into inclusive civic dispositions. The originality of this study lies in its structured cross-national comparison and in the introduction of the concept of civic architectures to explain how constitutional regimes interact with pedagogical practice. The study contributes to global debates by challenging binary assumptions about religion and secularism in democratic education and by advancing a process-oriented account of multicultural citizenship formation.